EFEKTIVITAS PENGGUNAAN MODEL PICTURE AND PICTUR DALAM PEMBELAJARAN MENULIS TEKS BERITA SISWA KELAS VIII/B MTS NEGERI SIJENJANG KOTA JAMBI TAHUN AJARAN 2016/2017 - Anggi Pratiwi; Sainil Amral; Sumiharti Sumiharti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is to describe the use of picture and picturemodel in learning text writing at students class VIII/B MTS Negeri Sijenjang Kota Jambi Academic Year 2016/2017. The method of the research is qualitative descriptive. The data of this research is students test result in writing text about news. The technique of collection data is by using observation, interview, test, and documentation. The result of the interview that (1) there are 22 students who gained very good predicate in which the percentage is 61,11%, (2) there are 5 students who get good predicate in which the percentage is 13,89%, (3) there are 5 students who get fair predicate in which the percentage is 13,89% , and (4) there are 4 students who get fail predicate in which the percentage is 11,11%. So, it can be concluded that the students ability in writing news report text by using picture and pictureat students class VIII/B MTS Negeri Sijenjang Kota Jambi Academic Year 2016/2017 falls into good category in which the mean is 72.Key Words:picture and picture model, writing, report news text.